A high-strength conductive copper-nickel-cobalt-silicon alloy established based on a cluster method and its preparation process and application
Through the design and optimization preparation process of copper-nickel-cobalt-silicon alloy composition based on the cluster method, the problem of difficult performance control caused by the sensitivity of the C70350 alloy composition is solved, and high-quality alloys with high tensile strength and high conductivity are achieved, meeting the strict requirements of industrial applications.
Patent Information
- Application Number
- CN202410439205.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-04-12
AI Technical Summary
As a high-end integrated circuit lead frame material, C70350 (Cu-Ni-Co-Si) alloy is difficult to control due to its component sensitivity. The wide component intervals and element ratios stipulated by existing standards are unclear, which does not match the actual best performance area, and does not fully consider the synergistic effects between elements, which aggravates the problem of component optimization.
A copper-nickel-cobalt-silicon alloy established based on the cluster method is used to prepare alloys with high tensile strength and high conductivity by finely controlling element classification, proportion and number of atoms, combined with an optimized preparation process. This method clearly specifies the proportion range and number of atoms of Ni, Co, and Si elements. Based on the 256-atom supercluster model, it ensures the scientificity and advancedness of component design.
It achieves excellent matching of alloy performance, room temperature tensile strength reaches 860MPa, conductivity up to 50% IACS, and performance is better than traditional copper, nickel, cobalt, silicon, and Typical alloys, meeting the strict requirements for material strength and conductivity in various industrial applications, while reducing the difficulty of alloy design and avoiding the occurrence of unqualified products.
Smart Images

Figure BDA0004788522730000071 
Figure BDA0004788522730000072 
Figure HDA0004788522740000011
Abstract
Description
Technical Field
[0001] The invention relates to a CuNiCoSi alloy, which is widely used in connectors and high-performance integrated circuit lead frames, has excellent tensile strength, good electrical conductivity, and is a non-magnetic alloy. Background Art
[0002] With the booming development of the electronic information industry, the scale and integration of integrated circuits are also growing. Lead frames have stricter standards for the strength and conductive quality of their materials because they are a key part of supporting chips and building integrated circuits. Due to its good resistance to high-temperature softening and excellent electrical conductivity, C70350 (Cu-Ni-Co-Si) alloy has gradually replaced the original beryllium copper, chromium copper and iron copper alloys to become a new generation of high-end integrated circuit lead frame materials. However, since C70350 alloy is a composition-sensitive alloy, a slight change in the composition ratio will lead to a huge change in the alloy performance, so the alloy performance is difficult to control.
[0003] According to the "Research Report on the Development Status and Market Prospects of China's Copper Alloy Lead Frame Materials Industry", as integrated circuits develop towards large-scale and ultra-large-scale, the increase in integration and the reduction in line spacing require the tensile strength of lead frame materials to reach more than 600MPa and the conductivity to be around 50%IACS. In the US ASTM standard, the composition ranges of the second phase elements Ni, Co and Si in C70350 alloy are (1.0-2.0)wt.%, (1.0-2.0)wt.%, and (0.5-1.0)wt.%, respectively. Based on this, my country revised the national standard GB / T5231-2022 "Processing Copper and Copper Alloy Grades and Chemical Composition" in October 2022. The Ni, Co, and Si element composition ranges of the BSi2-0.8 alloy are (1.0-2.5) wt.%, (1.0-2.0) wt.%, and (0.5-1.2) wt.%, respectively. Its composition range is exactly the same as the C70350 alloy composition range of the US UNS standard. The Ni, Co, and Si element composition ranges of the CuNi1Co1Si alloy in the German DIN standard are (1.0-2.0) wt.%, (0.5-1.0) wt.%, and (0.4-1.5) wt.%, respectively. In summary, the composition range of the C70350 alloy is both wide and narrow, and the proportion of the second phase elements is difficult to determine. Therefore, it is necessary to start from the source of the composition to solve the problem of alloy element composition matching.
[0004] By comparing the ranges of several national standards, it can be found that the range of Ni+Co in the German standard (DIN) is relatively narrow, at (1.61-3.22) at.%, while the range of Si is relatively wide, at (0.90-3.33) at.%, and the Cu residue is, for example Figure 1As shown. The Chinese national standard and the US UNS standard range are completely consistent, with the Ni+Co range of (2.14-4.82) at.%, the Si range of (1.12-2.67) at.%, and the Cu balance. The ASTM standard range is located at the lower left of the Chinese national standard range, with the Ni+Co range of (2.14-4.28) at.%, the Si range of (1.12-2.27) at.%, and the Cu balance. Combined with the experimental Cu-Ni-Co-Si alloy compositions reported by Pan et al. in Materials & Design (Accelerated discovery of high-performance Cu-Ni-Co-Si alloys through machine learning, Vol. 209, 2021, 109929), He Wei et al. in Materials Science and Engineering: A (Microstructure evolution and dislocation strengthening mechanism of Cu–Ni–Co–Si alloy, Vol. 826, 2021, 142023), and Li Jiang et al. in Materials Science and Engineering: A (Microstructure evolution and properties of aquaternary Cu–Ni–Co–Si alloy with high strength and conductivity, Vol. 766, 2019, 138390), it can be found that the actual alloy composition is mainly concentrated in a narrow area in the ASTM range (indicated by ×), while the national standard composition range is too wide, which also makes it difficult to optimize the composition of the alloy. Jiang et al. found that the mechanical properties of Cu-Ni-Co-Si alloys first increased and then decreased with the increase of Ni / Co ratio. When the mass ratio of Ni / Co increased from 1.12 to 1.95, the alloy showed higher mechanical properties, while the electrical conductivity continued to decrease with the increase of Ni / Co ratio. Zheng's research pointed out that when the mass ratio of Ni / Co increased from 0.32 to 1.95, the strength of Cu-Ni-Co-Si alloys increased from 630MPa to 720MPa, and the electrical conductivity decreased continuously from 48%IACS to 43%IACS. It can be found from previous studies that Cu-Ni-Co-Si alloy is a component-sensitive alloy with complex and difficult to understand composition rules. Even if the composition is selected within the national standard range, if the synergistic changes between Ni, Co and Si alloying elements and their effects on alloy properties are not considered, the fluctuation of alloy properties is still very obvious.Therefore, we urgently need to find the optimal composition point and appropriate composition ratio of C70350 alloy. Mechanistically, the above engineering problems originate from people's understanding of solid solution structure. As we all know, industrial alloys are based on solid solutions, which have chemical near-process as their structural characteristics and have both order and disorder. The alloy composition must be implicit in this near-process structure, but the academic community lacks a structural model for the chemical near-process of solid solutions.
[0005] In summary, according to the investigation of background technology, it is found that C70350 (Cu-Ni-Co-Si) alloy, as a high-end integrated circuit lead frame material, is difficult to control due to its composition sensitivity. The wide composition range specified in the existing standards has an unclear relationship with the element ratio, which does not match the actual performance optimal area, and does not fully consider the synergistic effect between elements, which exacerbates the difficulty of composition optimization. In addition, the lack of understanding of the solid solution structure and the lack of an effective structural model restrict the precise regulation of alloy properties. These problems urgently need new and effective technical solutions proposed by technical personnel in this field to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide a high-strength conductive copper-nickel-cobalt-silicon alloy based on a cluster method and its preparation process and application, wherein the composition control strategy is based on a unique local structural unit model. The model is centered on a supercluster containing 256 atoms, and its structure clarifies the positions and relationships of alloy elements within the supercluster.
[0007] The present invention strictly stipulates the ratio range and atomic number range of Ni, Co, and Si elements in the super cluster. These parameters are based on existing patent documents, ensuring the scientificity and advancement of the composition design. Through this precise control of the composition ratio, the present invention not only simplifies the complex alloying process of the solid solution alloy, but also effectively standardizes the selection of alloying elements within the ASTM standard range, avoiding the risk of unqualified products that may still appear while meeting the requirements of industrial standards. Based on this, the present invention derives the relationship between the composition range and the ratio change of each element and between the elements in the copper-nickel-cobalt-silicon alloy, and proposes a new alloy design method, which can solve the problem that the existing copper-nickel-cobalt-silicon alloy elements are difficult to control, and reduce the difficulty of alloy design for those skilled in the art. And through the corresponding preparation process in this patent, samples under different states can be obtained, with high preparation efficiency, energy saving and excellent performance, which can meet different processing requirements.
[0008] To achieve the above object, the present invention provides the following technical solution: a copper-nickel-cobalt-silicon alloy established based on a cluster formula method, wherein the copper-nickel-cobalt-silicon alloying elements are divided into a matrix Cu element that enters a supercluster formula, precipitation strengthening elements Ni, Co, Si, and trace elements Pb, Fe, Zn, Mn, and Mg that do not enter the supercluster formula; the supercluster formula contains 256 atoms, and the element components that enter the cluster formula are converted into the number of 256 atoms, and the alloy general formula can be obtained as {A}={[Si-(Ni , Co,Cu) 12 ](Si,Cu)3} 1~2 {Cu 16} 14~15 .
[0009] The present invention clearly specifies the ratio range of Ni, Co and Si elements: 1.7≤(Ni+Co) / Si≤2.9at., such as Figure 1 As shown by the oblique dotted line in the middle; and the range of the number of atoms occupied by Ni, Co, and Si elements in the supercluster formula: 6≤Ni+Co≤11, 3≤Si≤5, the above ratio relationship and the range of the number of atoms are derived from patents US20040079456A1, US20090183803A1, WO2005028688A1, EP2371976A1, etc. This further standardizes the selection of alloy elements within the ASTM standard range, avoiding the disadvantage of products with substandard performance while meeting industrial standard requirements.
[0010] The present invention also discloses a copper-nickel-cobalt-silicon alloy, wherein the components of the alloy include, by weight percentage (wt.%): Ni content ranges from 1.1 to 1.8 wt. %; Co content ranges from 1.1 to 1.8 wt. %; Si content ranges from 0.5 to 0.9 wt. %; wherein the ratio of (Ni+Co) / Si ranges from 4.2±0.7, and all components meet the requirements of ASTM standards.
[0011] The present invention is characterized in that the new composition standard can ensure that a high-quality alloy with performance superior to that of the ASTM standard is obtained under the preparation process specified in the present invention; the process at least includes a solution treatment step, i.e., 900-1100°C / 4-6h, oil quenching or water quenching;
[0012] Further preferably, for the preparation process described above, hot rolling of 45-55% is further provided before the solution treatment step;
[0013] Further preferably, for the preparation process described above, a cold rolling step of 75-85% is further provided after the solution treatment step;
[0014] Further preferably, for the preparation process described above, an aging treatment of 400-500°C / 1.5-2.5h is provided after the cold rolling step;
[0015] Further preferably, the preparation process described above is hot rolling 50% + solution treatment (1000℃ / 5h, oil quenching or water quenching) + cold rolling 80% + aging (450℃ / 2h, furnace cooling or water quenching); the alloy prepared by this process has a room temperature tensile strength of 860MPa and an electrical conductivity of 50%IACS. A high-strength and high-conductivity alloy is obtained, and both the strength and electrical conductivity are higher than the 840MPa and 49%IACS of the typical copper-nickel-cobalt-silicon alloy produced in industry.
[0016] Another aspect of the present invention is to disclose the application of the copper-nickel-cobalt-silicon alloy, specifically including the application in the electronic and electrical fields, including electronic components, packaging and connection technologies in the fields of information technology and communications; in particular, the application of lead frames in integrated circuit packaging.
[0017] The idea of implementing the above technical solution is to use the "super cluster" design concept to design the composition of copper-nickel-cobalt-silicon alloys, and to finely control the element classification, proportion and number of atoms, combined with a set of optimized preparation process flows, in order to prepare copper-nickel-cobalt-silicon alloys with high tensile strength (860MPa) and high conductivity (50% IACS). These performance indicators are significantly better than traditional copper-nickel-cobalt-silicon Typical alloys. This high-strength and high-conductivity alloy can meet the stringent requirements of material strength and conductivity for a variety of industrial applications. At the same time, through precise composition design and process control, the difficulty of alloy design is reduced, and the production of unqualified products is avoided. The cluster model has been applied to the composition optimization of many industrial alloys, including copper alloys, nickel-based high-temperature alloys, high-temperature oxides, aluminum alloys, stainless steel, titanium alloys, etc., providing a new method for the composition design and material selection of solid solution alloys.
[0018] The present invention is characterized in that: in the copper-nickel-cobalt-silicon alloy, the elements are divided into the matrix Cu, the precipitation strengthening elements Ni, Co, Si, and the trace elements (Pb, Fe, Zn, Mn, Mg) that do not enter the cluster formula. According to the applicant's previous work, in the cluster formula, combined with the element interaction mode, when the solute and solvent elements are respectively used as the central atoms, a cluster formula containing 16 atoms can be calculated. Therefore, the general formula of the copper-nickel-cobalt-silicon alloy contains 16*16=256 atoms, which is called a super cluster formula.
[0019] The present invention uses the pseudo-ternary composition formula of Cu-(Ni+Co)-Si to represent the ASTM standard range of copper-nickel-cobalt-silicon alloy. When Ni+Co takes the highest value (2.00Ni, 2.00Co) within the industrial standard range, Si takes the maximum value of 1.00 and the minimum value of 0.50 respectively. (Ni+Co) 10.90 -Si 5.75 -Cu 239.35 and(Ni+Co) 10.96 -Si 2.88 -Cu 242.16 Similarly, when Ni+Co takes the lowest value (1.00Ni, 1.00Co) in the industrial standard range, Si takes the highest or lowest value. We can get the composition formula (Ni+Co) 5.46 -Si 5.76 -Cu 244.78 and(Ni+Co) 5.49 -Si 2.88 -Cu 247.63 . Draw a parallelogram by connecting these four points to form the boundary of the ASTM region (e.g. Figure 1 As shown). Taking the boundary of the parallelogram as the range boundary of the supercluster model design, it can be seen that the number of atoms of the (Ni+Co) element ranges from (5.46 to 10.96) and the number of atoms of the Si element ranges from (2.88 to 5.75). In the 256-atom supercluster formula, the number of atoms is an integer, so the number of atoms of the (Ni+Co) element ranges from (6 to 11) and the number of atoms of the Si element ranges from (3 to 5). Combined with the ratio range 1.7≤(Ni+Co) / Si≤2.9at. derived from patents US20040079456A1, US20090183803A1, WO2005028688A1, and EP2371976A1, 9 component points can be obtained. The specific composition formula is shown in Figure 1 Notes ①~⑨ in the figure.
[0020] The present invention is further characterized in that a new wt.% internal control standard of components is provided within the ASTM range: Ni (1.1-1.8), Co (1.1-1.8), Si (0.5-0.9), (Ni+Co) / Si=4.2±0.7.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The new cluster method is adopted to strictly stipulate the synergistic variation relationship of alloy components and the composition range of individual alloy elements, which fundamentally overcomes the shortcomings of composition uncertainty brought by traditional composition range and improves the existing preparation process with high efficiency and excellent performance. Specifically:
[0023] (1) The composition of the copper-nickel-cobalt-silicon alloy under the traditional industrial standard was refined, and the proportional changes between various elements were taken into consideration to achieve a good match between the alloy composition and performance.
[0024] (2) A two-level specification was designed according to the supercluster method, that is, under the premise of satisfying 1.05≤Ni / Co≤1.51at. and 1.66≤(Ni+Co) / Si≤2.89at., 6≤(Ni+Co)≤11 and 3≤Si≤5.
[0025] (3) The copper-nickel-cobalt-silicon alloy designed with the coordinated change relationship of element composition has excellent performance. After hot rolling 50% + solid solution (1000℃ / 5h, oil quenching or water quenching) + cold rolling 80% + aging (450℃ / 2h, furnace cooling or water quenching), the room temperature tensile strength of the alloy sample reaches 860MPa and the electrical conductivity is as high as 50%IACS. A high-strength and high-conductivity alloy is obtained, and both strength and electrical conductivity are better than the copper-nickel-cobalt-silicon Typical of ASTM and the national standard GB / T5231-2022 alloy.
[0026] (4) By changing the ratio of the second phase components of the alloy, the strength / resistivity ratio of the alloy can be controlled, and alloys with different properties can be obtained for application in different scenarios.
[0027] (5) New wt.% internal control standards for composition are given within the ASTM range: Ni (1.1-1.8), Co (1.1-1.8), Si (0.5-0.9), (Ni+Co) / Si=4.2±0.7. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a pseudo-ternary composition diagram of Cu-(Ni+Co)-Si for the composition of copper-nickel-cobalt-silicon alloys under the new supercluster design standard. The oblique dotted lines in the figure are example lines for (Ni+Co) / Si=1.66, 2, and 2.89, respectively. The parallelogram with a solid border is the national standard GB / T range for copper-nickel-cobalt-silicon. The US UNS standard range is the same as the GB / T range. The parallelogram with a dotted border is the ASTM standard range. The shaded area is the composition range that meets the requirements of ASTM and patents. The actual alloy composition is represented by a black cross, and the circle is the alloy composition point designed for the 256-atom supercluster. The specific composition is shown in Figures ①~⑨. DETAILED DESCRIPTION
[0029] The following examples will further illustrate the present invention.
[0030] According to the applicant's previous work, combined with the interaction mode between elements, it can be concluded that the super cluster formula contains 256 atoms. By converting the element composition entering the cluster formula into the number of 256 atoms, the alloy formula can be obtained as {A} = {[Si-(Ni , Co,Cu) 12 ](Si,Cu)3} 1~2 {Cu 16} 14~15 Combined with the limiting condition 1.66≤(Ni+Co) / Si≤2.89, 9 composition points are obtained. The specific composition is shown in Figure 1 Illustrations ①~⑨.
[0031] Example 1
[0032] The preparation method of the copper-nickel-cobalt-silicon alloy involved in this application is:
[0033] High-purity metal materials are used, and the copper-nickel-cobalt-silicon alloy of Examples 1-9 in Table 1 is prepared according to the mass percentage. The ingredients are melted at least twice in a vacuum medium-frequency melting furnace under the protection of an argon atmosphere to obtain an alloy ingot with a uniform composition and a mass of about 2 kg, and the mass loss during the smelting process does not exceed 0.1%. The alloy ingot is homogenized in a vacuum muffle furnace, and the homogenization temperature is 1000°C and the treatment time is 5h. Subsequently, hot rolling is carried out with a hot rolling deformation rate of 50%. After that, solution treatment is carried out at 975±15°C for 2h, and oil cooling or water cooling is carried out to room temperature. Next, cold rolling is carried out, and the final sheet is rolled to 2mm, and finally aging treatment is carried out at 450±50°C for 2h, and furnace cooling or air cooling is carried out to room temperature to obtain the final state sample.
[0034] The organizational structure and performance analysis method of the copper-nickel-cobalt-silicon alloy involved in this application are:
[0035] The final samples were metallographically prepared, and the microscopic morphology of the samples was preliminarily observed using a light microscope. The organizational structure of the samples was observed in detail using a transmission electron microscope, and a dispersed granular precipitate phase was observed. The phase composition of the alloy was analyzed using an X-ray diffractometer, and combined with TEM-EDS analysis, the second phase in the alloy was mainly (Ni, Co)2Si phase. The tensile strength of the samples was tested using a universal testing machine. The conductivity of the samples was tested using an SMP350 conductivity tester and converted into resistivity.
[0036] When the alloy component ratio satisfies the general formula {A}, the composition points of the copper-nickel-cobalt-silicon alloy are shown in Table 1.
[0037] Table 1 Composition of copper-nickel-cobalt-silicon alloy of Examples 1-9
[0038]
[0039] Table 2 Tensile strength and electrical conductivity of copper-nickel-cobalt-silicon alloys of Examples 1-9
[0040]
[0041] The influence of different composition ratios on the properties of copper-nickel-cobalt-silicon alloy can be observed by comparing and analyzing the data in Table 1 and Table 2. Although all Examples 1-9 follow the cluster design principle, the changes in the content of Ni, Co, and Si in the composition lead to significant differences in tensile strength, resistivity, and strength-to-resistance ratio.
[0042] 1. Composition sensitivity and design flexibility: It can be seen from Table 1-2 that, taking Example 1 and Example 2 as examples, when the Ni content increases from 1.17 at.% to 1.56 at.%, the tensile strength of the final alloy is 804 MPa and 732 MPa, respectively. At the same time, their corresponding electrical conductivities are 56.7% IACS and 45.9% IACS, respectively. This proves that this characteristic gives designers great flexibility, and they can quickly adjust the alloy composition to obtain the desired performance according to specific application requirements. From the composition point of view, Example 2 simply replaces the Co atom with a Ni atom on the basis of Example 1, which shows that copper-nickel-cobalt-silicon alloy is a composition-sensitive alloy, and slight changes in the composition ratio will lead to large changes in performance. Conventional trial and error methods, Hume-Rothery rules, etc. cannot meet the needs of composition design. Only by using the supercluster model can the composition and performance of the alloy be directly linked from the perspective of atoms.
[0043] 2. A wide range of performance control: Table 2 shows the tensile strength, resistivity and strong resistance ratio of 9 examples, which cover a wide range of performance. For example, the tensile strength ranges from 614MPa (Example 4) to 862MPa (Example 8), the conductivity ranges from 3.04×10^(-8)Ωm (Example 1) to 4.24×10^(-8)Ωm (Example 7), and the strong resistance ratio ranges from 177 (Example 4) to 254 (Example 8). This wide range of performance control shows that alloys based on cluster design can achieve a variety of performance combinations from high conductivity and low strength to high strength and low conductivity, meeting the needs of different application scenarios, and demonstrating the wide applicability of cluster design in performance control.
[0044] 3. Full utilization of synergistic effects: Cluster design not only focuses on the role of individual elements, but also places special emphasis on the synergistic effects between elements. In the supercluster structures of different embodiments in Table 1, the number of atoms of elements such as Ni, Co, and Si does not change in isolation, but follows a certain proportional relationship, such as the ratio range of (Ni+Co) / Si. The data in Table 2 show that by carefully designing these proportional relationships, the synergistic effects between elements can be maximized, thereby obtaining optimized mechanical and electrical properties. This is different from the traditional method that may rely more on the adjustment of the addition amount of a single element, which reflects the advantage of cluster design in the deep understanding of the microstructure of the alloy.
[0045] 4. Simplification of complex alloy systems: Although copper-nickel-cobalt-silicon alloy is a complex multi-element alloy system, the supercluster structure model in Table 1 simplifies it into structural units that are easy to understand and operate. This simplification allows designers to focus on key local structures and adjust the element distribution within the supercluster to achieve regulation of the overall alloy performance. This simplification strategy helps reduce design variables and improve design efficiency. Compared with the complex composition space exploration that may be faced in traditional methods, it demonstrates the efficiency of cluster design in dealing with complex alloy systems.
[0046] Since strength and conductivity are a pair of inverse properties, we convert conductivity into resistivity and use the strength / resistivity ratio as a single coefficient to evaluate the performance of copper-nickel-cobalt-silicon alloy. The specific values are shown in Table 2. This ratio is named the strength-resistance ratio.
[0047] The strong resistance ratio of the copper-nickel-cobalt-silicon industrial alloy from Wieland of Germany and DOWA Metal Technology Co., Ltd. of Japan was calculated and fitted, and it was found that the strong resistance ratio of the industrial alloy was 239Mpa / 10 -8 Ωm. Comparing the strong resistance ratio of the supercluster designed alloy with that of the industrial alloy, it can be found that the strong resistance ratio of the alloys of Examples 1, 5, and 8 is better than that of the industrial alloy. Figure 1, the alloys of Examples 1, 5, and 8 correspond to the hollow circle composition points 1, 5, and 8 in the figure, that is, taking 5 as the target composition point, along the direction of (Ni+Co) / Si=2at., excellent performance can be obtained up to 1 and 8. Therefore, we can take the composition point 5 as the center to obtain the target composition point Cu-Ni4±0.5-Co4±0.5-Si4±0.5 (the lower right subscript indicates the number of atoms occupied by the current element in the 256-atom supercluster, and the number of Cu atoms is the remainder, the same below), and convert the atomic ratio into mass percentage Cu-(1.46±0.18)Ni-(1.47±0.18)Co-(0.70±0.09)Si wt.%. Similarly, when we go to the lower left of the composition diagram to the 1-component point, we get the lower limit of the supercluster design composition range Cu-Ni3-Co3-Si3, that is, Cu-1.09Ni-1.10Co-0.52Si wt.%; when we go to the upper right of the composition diagram to the 8-component point, we can get the upper limit of the supercluster design composition range Cu-Ni5-Co5-Si5, that is, Cu-1.83Ni-1.84Co-0.88Si wt.%. Therefore, the range of the supercluster design composition range is
[0048] Cu-(1.09~1.83)Ni-(1.10~1.84)Co-(0.52~0.88)Si wt.% In summary, the copper-nickel-cobalt-silicon alloy under the new standard provided by the present invention has the following creativity compared with the prior art: with the goal of obtaining a high-performance Cu-Ni-Co-Si alloy for lead frames, the composition of the copper-nickel-cobalt-silicon alloy is analyzed and optimized using a 256-atom supercluster model. The target material is obtained by melt casting combined with subsequent heat treatment processes, and the composition formula model, microstructure, and electrical (mechanical) properties are closely combined to obtain an analytical model for the composition design of a high-performance copper alloy, and a new standard for internal control of the composition is obtained within the ASTM range.
[0049] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A high-strength conductive copper-nickel-cobalt-silicon alloy established based on a cluster method, characterized in that: The alloy is composed of a matrix Cu element, precipitation strengthening elements Ni, Co, Si, and trace elements Pb, Fe, Zn, Mn, and Mg that do not enter the supercluster formula; wherein the copper-nickel-cobalt-silicon alloy is established using a cluster formula method, the supercluster formula contains 256 atoms, and the alloy general formula is expressed as {A}={[Si-(Ni , Co,Cu) 12 ](Si,Cu)3} 1~2 {Cu 16 } 14~15 , and the element composition entering the supercluster formula is converted to the corresponding number of 256 atoms; and the ratio range of Ni, Co, and Si elements is: 1.7≤(Ni+Co) / Si≤2.9at.; and the number of atoms occupied by Ni, Co, and Si elements in the supercluster formula is: 6≤Ni+Co≤11, 3≤Si≤5; The alloy comprises, by weight percentage: Ni content ranging from 1.1 to 1.8 wt. %; Co content ranging from 1.1 to 1.8 wt. %; Si content ranging from 0.5 to 0.9 wt. %; wherein the ratio of (Ni+Co) / Si ranges from 4.2±0.7, and all components meet the requirements of ASTM standards.
2. The process for preparing the alloy according to claim 1, characterized in that: The process at least includes a solution treatment step, 900-1100°C / 4-6h, and oil quenching or water quenching.
3. The preparation process according to claim 2, characterized in that: A step of hot rolling 45-55% is also provided before the solution treatment step.
4. The preparation process according to claim 2, characterized in that: A step of cold rolling 75-85% is also provided after the solution treatment step.
5. The preparation process according to claim 2, characterized in that: After the cold rolling step, an aging treatment step of 400-500°C / 1.5-2.5h is also provided.
6. The preparation process according to claim 2, characterized in that: First, the alloy is hot rolled 50%, followed by solution treatment, wherein the solution temperature is 1000°C, the holding time is 5 hours, and then oil quenching or water quenching is performed; then the solution treated alloy is cold rolled 80%, and finally aging treatment is performed, wherein the aging temperature is 450°C, the holding time is 2 hours, and after completion, it is cooled by furnace cooling or water quenching.
7. Application of the high-strength conductive copper-nickel-cobalt-silicon alloy established based on the cluster method as claimed in claim 1 in the fields of electronics, electrical engineering, information technology and communications.
8. The use according to claim 7, characterized in that: The alloy has a tensile strength of higher than 840 MPa and an electrical conductivity of higher than 49% IACS at room temperature, and is used in the fields of electronic components, packaging and connection technology.
Citation Information
Patent Citations
Cu-ni-si-co based copper ally for electronic materials and manufacturing method therefor
EP2371976A1
Copper alloy containing cobalt, nickel and silicon
US20040079456A1
Copper-nickel-silicon alloys
US20090183803A1
Process for high strength, high conductivity copper alloy of CU-ni-si group
WO2005028688A1
C70350 alloy for determining component collaborative change relation based on cluster type method and preparation method of C70350 alloy
CN115821110A